Data minning, data warehousing and olap - Sharma, Gajendra (S.K.Kataria, 2009)
Data minning, data warehousing and olap / Sharma, Gajendra. -- New Delhi: S.K.Kataria, 2009 004 Sh532 2nd ed No. of Copies : 1